Climate change detection in four locations in peninsular Malaysia for green sustainability awareness / Noor Kesuma Mohd Yazid ... [et al.] - Mohd Yazid, Noor Kesuma; Shaadan, Norshahida; Mohamad Hamzah, Firdaus; Ibrahim, Nurain Ibrahim; M.Mansor, Mahayaudin (Universiti Teknologi MARA, 2025)
Climate change impacts ecosystems, often resulting in the extinction of many species and their habitats and harm to human health. Preserving and protecting green spaces is essential to maintaining ecosystem health. This study aims to detect and examine climate change and its impact on temperature and rainfall at four locations in Malaysia to increase green environment sustainability awareness. The methodology involved investigating the pattern of climate variation using several visualization tools, the Mann-Kendall test, the EWMA control chart, and the Kruskall-Wallis test. Data on monthly average temperature and rainfall amount for the 30 years between 1989 and 2018 was obtained from the Department of Meteorology in Petaling Jaya. The study locations are Ipoh in Perak, Kuala Krai in Kelantan, Mersing in Johor, and Temerloh in Pahang, Peninsular Malaysia. To evaluate climate change, the 30 years of monthly data are divided into three cohorts: Cohort 1 (19891998), Cohort 2 (1999-2008), and Cohort 3 (2009-2018). The analysis confirms that climate change is evident across all four study locations. Mersing exhibited the highest rate of change in mean temperature, with an increase of 0.94% in Cohort 2 and 2.45% in Cohort 3 compared to Cohort 1. Meanwhile, Ipoh recorded the greatest rate of change in mean rainfall, with an increase of 20.62% in Cohort 2 and 19.91% in Cohort 3, compared to Cohort 1. The study findings support the need for green environment awareness among all Malaysians and an increased effort to educate and implement the love for nature in the general public so that our green environment can be sustained.